2017
DOI: 10.1051/e3sconf/20172200209
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency of a solar domestic hot water system

Abstract: Abstract. The solar domestic hot water (SDHW) system located on the campus of Bialystok University of Technology is the object of the research described in the current paper. The solar thermal system is composed of 35 flat plate collectors, 21 evacuated tube collectors and eight hot water tanks with the capacity of 1 m 3 of each. Solar facility is equipped with hardware for automatic data collection. Additionally, the weather station located on the roof of the building provides measurements of basic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…After determining the demand of domestic hot water EDHW and the solar fraction coefficient [8] and calculating the Esc value from Equation (1) or Equation 2, one can determine the required area of solar collectors : The procedure for estimating the required area or number of solar collectors based on the Esc value is described below.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After determining the demand of domestic hot water EDHW and the solar fraction coefficient [8] and calculating the Esc value from Equation (1) or Equation 2, one can determine the required area of solar collectors : The procedure for estimating the required area or number of solar collectors based on the Esc value is described below.…”
Section: Resultsmentioning
confidence: 99%
“…Mostly designers assume an SCF value between 40% and 60%. This factor has lower values for tall buildings due to the small roof area in relation to the number of inhabitants [8]. In the case of a very good intensity of solar radiation, sometimes even 100% energy coverage for hot water by the solar collector system is analysed [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows the distribution of in Poland using flat plate panels, and Figure 3 applies to evacuated tube collectors. Knowing the demand of domestic hot water QDHW, solar fraction SF coefficient [7], and calculating the value (Equation (1) or Equation (2)), one can determine the required area of solar collectors • m 2 .…”
Section: Results and Their Discussionmentioning
confidence: 99%
“…The test object is located on the roof of the Hotel for Research Assistants on the campus of Bialystok University of Technology (Poland), and includes 21 evacuated tube collectors, 35 flat plate collectors with the total gross area of almost 150 m 2 , and eight tanks with a total capacity of 8 m 3 . Description of the research facility, and the project under which it was built, can be found in [6,7]. The EnergyPlus v. 8.3 software was used to carry out these simulations.…”
Section: Description Of the Methods To Determine The Annual Energy Outmentioning
confidence: 99%